The Ideational Unity of Literary Text from the Psycholinguistic Perspective - Dyachuk, Nataliya (East European Journal of Psycholinguistics, 2015)
The article focuses on the ideational unity analysis of the literary text. The ideational unity is viewed through the main psycholinguistic features of the literary text: integrity and coherence. The original text and three target versions were analyzed. The Smile by R. Bradbury and its Ukrainian versions made by professional translators Lada Kolomiyets, Andriy Yevsa, Yaroslav Vepryniak were the principal sources of the analysis. The empirical research results of the ideational unity of the literary texts were given in the article. The description of the research methods used for integrity and coherence analysis in the chosen literary texts was represented. The figurative analysis of the ideational unity existence in literary text was given in the article. References Nussbaumer, A. (1994). Studienbuch Linguistik. Tübingen: Niemeyer Zavhorodnia, L (2009). Textoznavstvo [Text Studies]. Cherkasy: Brama-Ukraina Zimnyaya, I. (2001). Lingvopsichologiya Rechevoy Deyatelnosti [Linguopsychology of Speech Activity]. Voronezh: Modek. Yakhibbaeva, L (2008). Kategorii tselnosti / tselostnosti i svyaznosti kak osnovnye priznaki teksta [Categories of Integrity and Coherence as the Basic Features of a Text]. Lingvokulturologia, 2, 209–214. Leontyev, A. (2005). Psikholingvistichiskie edinitsi i porozhdenie rechevogo vuskazuvaniya [Psycholinguistic Units and Speech Utterance Production]. Moscow: Editorial URSS. Moskalskaya, O. (1981). Grammatika Teksta [Text Grammar]. Moscow: Vysshaya Shkola. Novikov, A. (2003). Tekst i «kontrtekst»: dve storony protsessa ponimaniya. Journal of Psycholinguistics, 1, 64–76. Sorokin, Yu. (1985). Psicholingvisticheskie Aspekty Izucheniya Teksta [Psycholinguistic Aspects of Studying Text]. Moscow: Nauka. Stepanova, M. (2008). Kogeziya i kogerentnost v britanskom mediadiskurse. Philologiya, 333–335. Sources Bradbury R. (1983) Fahrenheit. Short Stories. Moscow: Raduga Publishers. Bradbury, R. The Smile. Retrieved from http://raybradbury.ru/library/story/52/9/1/. Bradbury, R. (1999a). Ousmishka [The Smile]. transl. by L. Kolomiyets. Vsesvitnia Literatura v Serednikh Navchalnykh Zakladakh Ukrainy, 3(227), 11–12. Кyiv: Pedahohichna Presa,. Bradbury, R. (1999b). Ousmishka [The Smile]. transl. by Yaroslav Vepryniak. Zarubizhna Literatura. 6th Form. Textbook. 296–300. Ternopil’: Navchal’na Knyha–Bohdan. Bradbury, R. (2011). Ousmishka [The Smile]. transl. by Andriy Yevsa. Svitova Literatura. 6th Form. Textbook, 374–381. Kharkiv: FOP Spivak.